Comparative efficacy of different estrus synchronization protocols on estrus induction response, fertility and plasma progesterone and biochemical profile in crossbred anestrus cows - Dhami, A. J. (Vet World, 2015)
AIM: To evaluate estrus induction response and fertility including plasma progesterone and biochemical profile following use of three standard hormonal protocols in anestrus crossbred cows. MATERIALS AND METHODS: The study was carried out on 40 true anestrus and 10 normal cyclic cows. 10 anestrus cows each were treated with standard intravaginal controlled internal drug release (CIDR) device, Ovsynch (GPG) protocol, and Norgestomet ear implant with fixed-time artificial insemination (FTAI). 10 anestrus cows were kept as untreated control while 10 cows exhibiting the first estrus within 90 days postpartum without any treatment served as normal cyclic control. Blood samples were obtained from treated cows on day 0, 7, 9 (AI) of treatment and day 21 post-AI, and from control groups on the day of AI and day 21 post-AI for estimation of plasma progesterone, protein, cholesterol, calcium, and inorganic phosphorus profile. RESULTS: The use of CIDR, Ovsynch, and Norgestomet ear implant protocols resulted in 100% estrus induction with conception rates at induced estrus of 60%, 50%, and 50%, and the overall of three cycles as 80%, 80%, and 70%. In untreated anestrus control (n=10), only three cows exhibited spontaneous estrus within 90 days of follow-up and conceived giving the first service and overall conception rates of 66.66% and 30.00%, respectively. In normal cyclic control (n=10), the conception rates at first and overall of three cycles were 50% and 80%. The overall mean plasma progesterone (P(4)) concentrations in anestrus cows studied on day 0 (initiation), 7 (prostaglandin injection and/or removal of implant), 9 (FTAI) of treatment and on day 21 post-AI revealed that the values on day 7 and 21 were significantly (p<0.01) higher than other two periods in all three groups. The concentrations were significantly (p<0.05) higher in conceived than non-conceived group on day 21 post-AI in CIDR (4.36±0.12 vs. 1.65±0.82 ng/ml) and Ovsynch (4.85±0.62 vs. 1.59±0.34 ng/ml), but not in Norgestomet ear implant (4.50±0.53 vs. 3.02±1.15 ng/ml) or normal cyclic group (5.39±0.67 vs. 3.13±0.37 ng/ml). The cholesterol and protein levels were significantly higher, but not the calcium and phosphorus, in normal cyclic control than in anestrus groups. The influence of treatment days and pregnancy status was not significant for any of the biochemical constituents in any of the groups. CONCLUSION: Ovsynch and/or CIDR synchronization protocol can be effectively used to improve fertility up to 80% in anestrus cows, as compared to 30% in anestrus control, combined with plasma progesterone to delineate the reproductive status before and after treatment.